Autoeficácia de Mães Chefes de Famílias Monoparentais - Brandão, Rosane Neves (2024)
There are several reasons why men and women assume single parenthood, a condition in which only one parent resides with the children in the same household. This situation may result from divorce, widowhood, adoption, personal choice, or abandonment. Regarding female single parenthood, the number of families headed by women has almost doubled in the last two decades. Statistics indicate that many of these families live below the poverty line, highlighting that female single parenthood is still associated with various social vulnerabilities. In these circumstances, women often find themselves overwhelmed, having to balance domestic responsibilities, child rearing, and household support. This study is based on Bandura's social cognitive theory and explores the concept of self-efficacy, defined as an individual's belief in their own ability to organize and execute certain actions to achieve a desired outcome, influencing their ability to resist environmental pressures without resulting in dysfunctionality. As agents, individuals can perceive environmental threats as opportunities, selecting strategies to deal with them. The aim of this study is to investigate the self-efficacy of single mothers served at the Social Assistance Centers (CRAS) in the municipality of Vitória, ES, Brazil. Thirty women responsible for single-parent families for more than a year participated in the research, whose children, infants, and/or adolescents live in situations of social vulnerability. To achieve the proposed objectives, interviews were conducted with the aid of a semistructured script, aiming to explore these women's experiences and self-efficacy. Data analysis of the interviews was performed through Categorical Thematic Content Analysis, using coding and data processing. The results indicated that the self-efficacy of single mothers is related to their past experiences, emotional state, behavioral influences, and opinions of others. Thus, it was observed that these women construct their perceptions of self-efficacy from four main sources: (1) mastery experiences, (2) vicarious experiences, (3) social persuasions, and (4) physiological and affective states. Therefore, this study contributes to a better understanding of the self-efficacy of single mothers and can serve as a basis for the development of public policies that promote the rights of families led by women in situations of social vulnerability.